Self‐Optimization of the Active Site of Molybdenum Disulfide by an Irreversible Phase Transition during Photocatalytic Hydrogen Evolution. Issue 26 (23rd May 2017) - Wang, Longlu; Liu, Xia; Luo, Jinming; Duan, Xidong; Crittenden, John; Liu, Chengbin; Zhang, Shuqu; Pei, Yong; Zeng, Yunxiong; Duan, Xiangfeng
Abstract: The metallic 1T‐MoS2 has attracted considerable attention as an effective catalyst for hydrogen evolution reactions (HERs). However, the fundamental mechanism about the catalytic activity of 1T‐MoS2 and the associated phase evolution remain elusive and controversial. Herein, we prepared the most stable 1T‐MoS2 by hydrothermal exfoliation of MoS2 nanosheets vertically rooted into rigid one‐dimensional TiO2 nanofibers. The 1T‐MoS2 can keep highly stable over one year, presenting an ideal model system for investigating the HER catalytic activities as a function of the phase evolution. Both experimental studies and theoretical calculations suggest that 1T phase can be irreversibly transformed into a more active 1T′ phase as true active sites in photocatalytic HERs, resulting in a "catalytic site self‐optimization". Hydrogen atom adsorption is the major driving force for this phase transition. Abstract : An irreversible phase transition of MoS2 during the photocatalytic hydrogen evolution was decrypted. Hydrogen atom adsorption is the driving force for this phase transition. The distorted structure could be stabilized by both strain and S vacancies. This phase‐transition‐induced catalytic activity improvement was defined as a "self‐optimization" mechanism.